Antifouling Modification of Gold Surfaces for Acoustic Wave Sensor Applications - Aries Delica; Mikhail A. Nazarov; Brian De La Franier; Michael Thompson (Biosensors)
This study aims to develop a robust and reproducible method for fabricating efficient ultrathin antifouling coatings on gold surfaces by leveraging hydroxylation-based surface modifications. An ultrathin antifouling coating of a monoethylene glycol silane derivative, known to reduce fouling by at least 90% on flat hydroxylated surfaces, was successfully replicated on flat gold (reducing fouling by ~75%) by hydroxylating its surface with β-mercaptoethanol. This tandem coating contains the monoethylene glycol silane layer on top of the β-mercaptoethanol on the gold. Characterization was performed using contact angle goniometry, atomic force microscopy, x-ray photoelectron spectroscopy, and antifouling measurements. The results from these techniques, consistent with the literature, confirmed the successful and reproducible application of the tandem coating. Through heterogeneities, including defects and incomplete coverage, the AFM data revealed distinct visible layers of the tandem coating. The direct application of monoethylene glycol silane onto gold resulted in superior antifouling performance (88% reduction), demonstrating that direct silylation exploits pre-existing oxygen-containing species on the gold surface for a more effective antifouling layer. These findings offer a scalable approach for engineering antifouling coatings on gold substrates, with potential applications in biosensing and implantable device antifouling technologies.